Kinetic studies of laccase enzyme of Coriolus versicolor MTCC 138 in an inexpensive culture medium - Mishra A.; Kumar S. (My University, 2025)
An attempt was made to use cyanobacterial biomass of water bloom, groundnut shell (GNS) and dye effluent as culture medium for laccase enzyme production by Coriolus versicolor. Laccase production was found to be 10.15 ± 2.21 U/ml in the medium containing groundnut shell and cyanobacterial bloom in a ratio of 9:1 (dry weight basis) in submerged fermentation at initial pH 5.0 and 28 ± 2 °C temperature. Half life of enzyme was found to be 74 min at 60 °C. Kinetic analysis of laccase when made with substrate ABTS, Km and Vmax were found to be 0.29 mM and 9.49 μmol/min respectively. Azide and hydroxylamine were found to exert significant inhibition on thermostable laccase. Inhibitor constant (ki) for azide and hydroxylamine were 1.33 and 0.18 mM respectively. This study forms the first report on the potential application of waste water cyanobacterial bloom and dyeing effluent as a medium for laccase production by C. versicolor MTCC138. © 2009 Elsevier B.V. All rights reserved.